Evaluating the Effectiveness of TOD (Truth or Dare) Roy's Educational Card on Self-Confidence Levels Among Midwifery Students : A Randomised Controlled Trial - Kurnia Indriyanti Sari; Nuris Kushayati; Kiftiyah Kiftiyah (Universitas Islam Lamongan, 2026)
Low self-confidence and high anxiety regarding the OSCE pose significant psychological challenges for midwifery students, which impact the quality of midwifery care. Innovative gamification-based interactive learning media are needed to address this issue. Objective: This study aims to evaluate the effectiveness of Roy’s Truth or Dare (TOD) Educational Cards in improving self-confidence and reducing anxiety regarding the OSCE among midwifery students. This research is a double-blind randomized controlled trial (RCT) involving 246 midwifery students from East Java (Kediri, Jombang, Mojokerto, Sidoarjo). Participants were randomly assigned to the intervention group (n=123), which received Roy’s TOD Educational Cards for 4 weeks (60 minutes per session, twice weekly), and the control group (n=123), which received conventional instruction. Measurements were taken at baseline, post-test (4 weeks), and follow-up (4 weeks post-intervention) using the General Self-Efficacy Scale (GSES), the Confidence in Clinical Skills Scale (CCSS), and the Westside Test Anxiety Scale (WTAS). Data analysis used the independent t-test and the Mann-Whitney U test based on the results of the Shapiro-Wilk normality test. The intervention group showed a significant increase in GSES scores (α =14.3 points) compared to the control group (Δ=3.3 points), with p<0.001. The intervention group’s CCSS score increased by 20.7 points, while the control group’s increased by only 5.2 points. The decrease in WTAS scores in the intervention group (α=11.2 points; p<0.001) was much greater than in the control group (α =2.7 points; p=0.142). The intervention effect was sustained at the 4-week follow-up (p<0.001), with a very high level of student satisfaction (mean 4.6 out of 5). Roy’s TOD (Truth or Dare) Educational Cards are effective in significantly and sustainably boosting self-confidence and reducing anxiety among midwifery students in preparation for the OSCE. This tool is recommended as an innovative learning method in midwifery education institutions.